PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN IPA MATERI MENDESKRIPSIKAN DAUR HIDUP HEWAN DI LINGKUNGAN SEKITAR SISWA KELAS IV SEKOLAH DASAR - Permana, Erwin Putera; Nourmavita, Desy (UNIB Press, 2017)
This research is motivated by the observation in grade IV of elementary school of Natural Science subject (IPA) animal life cycle, because most students experience saturation in learning because the teacher still use conventional teaching method that is lecture. In addition, the source of student learning comes only from teachers and textbooks alone without any use of instructional media. Teachers do not pay attention to the explanations of teachers and students do not understand the material being taught. This research is a research development or research and development (R & D) adapted from the ADDIE development model. The stages are 5 stages: 1) Analysis (Analysis), Development (Design), Implementation (Implementation), and Evaluation (Evaluation). Validation is done by material experts, media experts, and learning practitioners. The results of this study are (1) Development of Interactive Multimedia Life Cycle Animals using professional adobe flash CS6 application with the method of ADDIE model development. (2) The teacher's response to this media is the optimism of teachers to achieve the learning objectives, as well as the students' response to this media is very positive, they are very fond of this media. (3) Interactive multimedia from the big aspect based on the percentage of the feasibility assessment in the category is very appropriate to be used as learning media of Natural Science for fourth grade students of elementary school. Based on the conclusions of the results of this study, namely: (1) For teachers, can use interactive multimedia to help students become more active and can create a fun classroom atmosphere. (2) For further research, make a broad try again, in order to produce learning media that can be used widely.